Cardiorespiratory fitness and ideal cardiovascular health in European adolescents. Issue 10 (8th December 2014) - Ruiz, Jonatan R; Huybrechts, Inge; Cuenca-García, Magdalena; Artero, Enrique G; Labayen, Idoia; Meirhaeghe, Aline; Vicente-Rodriguez, German; Polito, Angela; Manios, Yannis; González-Gross, Marcela; Marcos, Ascensión; Widhalm, Kurt; et al.
Abstract : Objective: We studied in European adolescents (i) the association between cardiorespiratory fitness and ideal cardiovascular health as defined by the American Heart Association and (ii) whether there is a cardiorespiratory fitness threshold associated with a more favourable cardiovascular health profile. Methods: Participants included 510 (n=259 girls) adolescents from 9 European countries. The 20 m shuttle run test was used to estimate cardiorespiratory fitness. Ideal cardiovascular health was defined as meeting ideal levels of the following components: four behaviours (smoking, body mass index, physical activity and diet) and three factors (total cholesterol, blood pressure and glucose). Results: Higher levels of cardiorespiratory fitness were associated with a higher number of ideal cardiovascular health components in both boys and girls (both p for trend ≤0.001). Levels of cardiorespiratory fitness were significantly higher in adolescents meeting at least four ideal components (13% higher in boys, p<0.001; 6% higher in girls, p=0.008). Receiver operating characteristic curve analyses showed a significant discriminating accuracy of cardiorespiratory fitness in identifying the presence of at least four ideal cardiovascular health components (43.8 mL/kg/min in boys and 34.6 mL/kg/min in girls, both p<0.001). Conclusions: The results suggest a hypothetical cardiorespiratory fitness level associated with a healthier cardiovascular profile in adolescents. The fitness standards could be used in schools as part of surveillance and/or screening systems to identify youth with poor health behaviours who might benefit from intervention programmes.